2009
DOI: 10.1007/s11010-009-0125-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing of GM3 synthase expression during differentiation of human blood monocytes into macrophages as in vitro model of GM3 accumulation in atherosclerotic lesion

Abstract: In previous studies, we showed that ganglioside levels (GM3 being the main ganglioside) in human aortic intima isolated from atherosclerotic lesions were 5 times greater compared to intima from non-diseased vascular areas. Recently, we found that GM3 and GM3 synthase levels in differentiated in vitro macrophages were five and ten times higher, respectively, compared to freshly isolated human monocytes. In this article, we report that GM3 synthase mRNA levels were significantly higher in differentiated human mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
8
0
2
Order By: Relevance
“…These findings, in conjunction with our earlier results [ 13 , 14 , 30 ], indicate a probable relationship between biosynthesis activation and, as a consequence, an increase in the level of gangliosides and a higher expression of lipid rafts in cultured macrophages compared to freshly isolated monocytes. An increasing amount of data confirms that monocytes are already pre-activated, circulating before their migration to inflammation areas during inflammatory pathologies accompanied by an increased production of cytokines, such as TNF-α, M-CSF, or IL-6 [ 10 - 12 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These findings, in conjunction with our earlier results [ 13 , 14 , 30 ], indicate a probable relationship between biosynthesis activation and, as a consequence, an increase in the level of gangliosides and a higher expression of lipid rafts in cultured macrophages compared to freshly isolated monocytes. An increasing amount of data confirms that monocytes are already pre-activated, circulating before their migration to inflammation areas during inflammatory pathologies accompanied by an increased production of cytokines, such as TNF-α, M-CSF, or IL-6 [ 10 - 12 ].…”
Section: Resultssupporting
confidence: 90%
“…Previously, we observed a significant increase in the synthesis of gangliosides during the in vitro differentiation of human monocytes into macrophages [ 14 ]. We also found that the mRNA level of GM3 synthase (a key enzyme of the ganglioside synthesis) was significantly higher in cultured monocytes/macrophages than in freshly isolated monocytes and in the intima of an atherosclerotic plaque compared to the intima of unaffected regions of the human aorta [ 30 ]. It should be noted that macrophages are the main cells in the intima of the atherosclerotic arteries, whereas they are actually absent in the normal intima.…”
Section: Resultsmentioning
confidence: 99%
“…Полученные данные позволяют сделать вывод о том, что повышение содержания GM3 -один из признаков активации моноцитов и лимфоцитов в крови пациентов с атеросклерозом. Так как этот признак характерен для дифференцированных макрофагов в культуре [11], можно предположить, что моноциты периферической крови пациентов с атеросклерозом приобретают некоторые свойства макрофагов.…”
Section: смр[unclassified
“…Подавление биосинтеза ганглиозидов специфическим ингибитором глюкозилцерамидсинтазы D-1-трео-1-фенил-2-пальмитоиламино-3-пирролидино-1-пропанолом приводит к нарушению процесса макрофагальной дифференцировки [11].…”
unclassified
“…In the human pre-myeloid leukemia cell line HL-60 and histiocytic lymphoma cell line U937, exogenous GM3 induces monocytic cell differentiation and notably, GM3 increase during macrophage-like cell differentiation [47]. GM3 synthase levels are significantly higher in human monocyte-derived macrophages than in monocytes and GM3 has been considered as a physiological modulator of macrophage differentiation in human atherosclerotic aorta [78]. In bone marrow-derived macrophages, peritoneal macrophages and the Raw264.7 macrophage cell line, exogenous GM1 contributes to the induction of arginase-1, a major M2 macrophage marker, and to the secretion of monocyte chemoattractant protein-1 (MCP-1) through CD206-mediated activation of signal transducer and activator of transcription (STAT) 6 [48].…”
Section: Inflammatory Cells and Gangliosidesmentioning
confidence: 99%